Myoepithelioma of the Vocal fold – A case report (Bombay Hospital Journal, 2024)
Background: Myoepithelioma of the vocal fold is an extremely rare, benign tumour with non-specific symptoms. To the best of our knowledge, we report the sixth case of myoepithelioma in larynx and the third benign larynx localization of myoepithelioma.Summary: We report a case of 16-year-old male presenting with hoarseness of voice. He came to our hospital with history of previous three surgeries; the histopathological examination reported as “Vocal Cord Polyp” and “Inflammatory Myofibroblastic Tumour”. Stroboscopy revealed a multilobulated vascular lesion attached to the left vocal process. CT scan showed a well demarcated focal nodular lesion arising from left true vocal cord, projecting into laryngeal lumen. Major laser surgery was performed under general anaesthesia in our hospital. The final histopathologic diagnosis was myoepithelioma (spindle cell type) of left vocal fold.Conclusion: The larynx is a very rare site for this type of tumour. Hence, it is crucial to make the correct diagnosis, as it can be confused with other spindle cell tumours which occur in the larynx.
Keywords: Myoepithelioma; Larynx; Vocal fold